Seleksi Wiraniaga Terbaik dengan Pendekatan Multi-Kriteria Metode ARAS dan SMART - Cahyono, Yono; Ikasari, Ines Heidiani; Khoirudin, Khoirudin (TIN: Terapan Informatika Nusantara, 2025)
The selection of the best salesperson is a critical component in enhancing sales performance and maintaining a company’s competitiveness. However, this process is often hindered by subjective assessments and difficulties in objectively comparing candidates. This study aims to apply two Multi-Criteria Decision Making (MCDM) methods, ARAS (Additive Ratio Assessment System) and SMART (Simple Multi-Attribute Rating Technique) to evaluate and rank 15 sales candidates based on six criteria: Work Quality, Creativity, Initiative, Teamwork, Expertise, and Cost Efficiency. Qualitative assessment data were converted into quantitative values and analyzed using both methods to obtain final scores and rankings. The results indicate that the top-ranked candidates using the ARAS method are Lia Husna (A7), Eriza (A13), and Dodi (A3), while the SMART method identifies Septian (A5), Zainal (A2), and Lia Husna (A7) as the top performers. The difference in rankings is attributed to the weight distribution and the methods’ sensitivity to attribute values—SMART emphasizes high values in heavily weighted criteria, whereas ARAS evaluates the relative ratio against the ideal solution. Correlation analysis between both methods reveals partial alignment, suggesting that integrating multiple approaches strengthens result validation. Overall, the dual-method approach enhances selection objectivity and provides a more robust foundation for strategic decision-making in salesperson performance management.